(untitled) (Journal of Hama University, 2019)
The aim of this research was to study the cryoprotective effect of addition of glutamine for freezing Awassi ram semen and to determine the optimal concentration of glutamine to improve the motility of spermatozoa for define a cryopreservation extender for ram sperm of an equivalent or superior quality to commercial extenders. This study was carried out at the laboratory of artificial insemination and embryo transfer in Ezra station Belongs to ACSAD. Six Awassi ram, 3-6 years old with body weight 79 ± 2.8 KG, were used. Semen was collected in breeding season by artificial insemination one/per week for 4 weeks. Glutamine was added in different concentrations to local diluents (Triladel© with egg yolk). The glutamine was added to 6 splite ejaculates at concentrations of (10, 20, 30, 40, 50 mM) in breeding season. The quality of frozen-thawed spermatozoa in each extender was analyzed using computer assisted semen analysis (CASA). The evaluated parameters were Mobility, Progressive, Distance Straight Line: (DSL), Velocity Average Path: (VAP), Curvilinear Line Velocity: (VCL), Straight Line Velocity: (VSL), linearity index: (LIN), and amplitude of lateral head displacement: (ALH). Results showed that the glutamine at a concentration of 20mM significantly improves the motility and (VCL, DSL) compared with other concentration and control extender.